# Math

posted by .

3/17x=12

• Math -

(3/17)x=12
x = 12/(3/17)
x = 12 * (17/3)
x = 204/3 = 68

• Math -

(3/17)x = 12
to get x alone, you divide both sides by the numerical coefficient (number before the variable) of x. 3/17 divided by itself is 1 and thus thus
x = 12 / (3/17)
to divide by fraction, you get the reciprocal of the divisor (that is, the 3/17) and change the division operation to multiplication:
x = 12 * 17/3
x = 68

hope this helps~ :)

• Math -

Thank-You

## Similar Questions

1. ### polynomials

(3+7x)-(16x2+15x2) (3+1x)-(12x+16+0+18x2) Q4: (15+13x2+14x2)+(13x+18x) Q5: (2x2+1+15x2+7+3)+(0x+17x) Q6: (18x+3)+(17x2+1x2+9+8+0x) Q7: (6x + 14) - (9x + 5) Q8: (14x2 + 13x + 12) - (7x2 + 20x + 4) Q9: Subtract -10x2 + 16x - 15 from …
2. ### polynomials

(3+7x)-(16x2+15x2) (3+1x)-(12x+16+0+18x2) Q4: (15+13x2+14x2)+(13x+18x) Q5: (2x2+1+15x2+7+3)+(0x+17x) Q6: (18x+3)+(17x2+1x2+9+8+0x) Q7: (6x + 14) - (9x + 5) Q8: (14x2 + 13x + 12) - (7x2 + 20x + 4) Q9: Subtract -10x2 + 16x - 15 from …
3. ### Algebra

(x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this is how far I got. The answer I know is -(5x^2-17x-9)/(x-3)(x+2) first I get (x)(x+2)/(x-3)(x+2)- (4)(x-3)(x+2)/(x-3)(x+2)-(2x-5)(x-3)/(x-3)(x+2) Then I get x^2+2x-4x^2-4x-24-2x^2-11x+15 …
4. ### Algebra

(x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this is how far I got. The answer I know is -(5x^2-17x-9)/(x-3)(x+2) first I get (x)(x+2)/(x-3)(x+2)- (4)(x-3)(x+2)/(x-3)(x+2)-(2x-5)(x-3)/(x-3)(x+2) Then I get x^2+2x-4x^2-4x-24-2x^2-11x+15 …
5. ### Algebra

Solve: 5x-3=11+12x; 17x-3=11; 17x-3+3=11+3= 17x=14; x= 14/17 is this right?
6. ### Math

Is this correct? The problem says perform the indicated operation. (9x^2-7x-66)+(8x^2+9x) I came up with this for the answear -66+2x+17x^2 or could it be 17x^2+2x-66
7. ### Algebra I

Thanks Reiny, but I'm still lost. I understand how you multipled by 10X on the right to get 17x, but you went too fast on the left, and I have no idea how you got 10x^2-20 from the starting left side. Can you show each step?
8. ### Math help Steve?

1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?
9. ### Math

1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?
10. ### Math

1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?

More Similar Questions